Projekt foresight w perspektywie regionalnej strategii innowacji - Tuziak, Arkadiusz (The Foresight Project in the Perspective of the Regional Strategy of Innovation, 2006)
The article undertakes the problems of the foresight project in the context of regional innovations. It shows the specificity and the essence of foresight as a new way of thinking about future, its serious understanding and active forming. It includes the characteristics of mutual beneficial connections between foresight and regional strategy of innovation. It emphasizes the complementarities and sequences of both undertakings oriented at the future.The practical aspect included in the article of characteristics and analysis is pointing out some areas of activities as far as regional foresight for the Podkarpacie district is concerned, which are crucial from the point of view of the modem, and balanced development of the region, at the same time constituting the lengthening of the time horizon and widening the scope of the research defined in the strategy of innovation for the Podkarpacie district.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 646-654